Configuring Generalized Form of Half Companion Sequence of Special Dio-Triples involving Centered Triacontagonal Number - Priya, S. Shanmuga; Janaki, G. (Communications in Mathematics and Applications, 2024)
In this paper, the generalized half companion sequence of a special Dio-3-tuple covering the centred triacontagonal number of different ranks with different properties are produced. Also, we analyze the extendability of 3-tuples to quadruples for some ranks by performing a suitable algebraic algorithm and various enthralling patterns are presented using MATLAB.